2021
DOI: 10.3390/ijerph18189697
|View full text |Cite
|
Sign up to set email alerts
|

EKC Test of the Relationship between Nitrogen Dioxide Pollution and Economic Growth—A Spatial Econometric Analysis Based on Chinese City Data

Abstract: During the just concluded 13th Five-Year Plan, China continued to maintain the momentum of rapid economic development, but still faced environmental pollution problems caused by this. Finding the relationship between Nitrogen Dioxide pollution and economic development is helpful and significant in better achieving and optimizing sustainable environmental development. Taking China’s 333 prefecture-level cities as samples from 2016 to 2018, the spatial lag model (SAR) was used to study the impact of economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The EKC assumes that environmental quality is initially degraded during the improvement of per capita income level, but gradually improves when the income reaches the inflection point, that is, the relationship between environmental quality and income is an inverted U-shaped [ 47 ]. Previous studies have shown that the EKC shows other trends, including type U, N, inverted N, monotonous decreasing, and monotonous increasing trends [ 14 , 18 ]. We found that the EKC of SO 2 emissions and per capita GDP in the YREB is N-shaped ( Figure 3 a) and that the 11 provinces in the YREB show N-shaped and inverted U-shaped curves ( Figure 3 b,c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EKC assumes that environmental quality is initially degraded during the improvement of per capita income level, but gradually improves when the income reaches the inflection point, that is, the relationship between environmental quality and income is an inverted U-shaped [ 47 ]. Previous studies have shown that the EKC shows other trends, including type U, N, inverted N, monotonous decreasing, and monotonous increasing trends [ 14 , 18 ]. We found that the EKC of SO 2 emissions and per capita GDP in the YREB is N-shaped ( Figure 3 a) and that the 11 provinces in the YREB show N-shaped and inverted U-shaped curves ( Figure 3 b,c).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have used this method to study the agglomeration characteristics of pollutants such as wastewater [ 14 ], carbon dioxide (CO 2 ) [ 15 ], fine particulate matter (PM 2.5 ) [ 16 ], and SO 2 [ 12 ], and have shown that there is a positive spatial autocorrelation of SO 2 concentration in China; that is, the SO 2 concentration in an area will increase because air pollutant spread is affected by nearby areas [ 9 , 12 ]. The EKC has been used to explain the relationship between pollutants and economic development, such as CO 2 [ 17 ], SO 2 [ 13 ], nitrous oxide (NO 2 ) [ 18 ], and wastewater [ 14 ]. According to the EKC, the relationship between national incomes and their contribution to environmental degradation resembles an inverted U-shaped curve [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Anselin, the Moran’s I can measure whether there is interdependence between variables in space [ 41 ]. Furthermore, Moran’s I has been widely utilized to examine spatial correlations of spatially adjacent regional units [ 42 , 43 ]. The specific formula is shown in Equation (1): where is the sample variance, is the ( , ) element of the spatial weight matrix, and the value of the Moran’s I is generally between −1 and 1.…”
Section: Methodsmentioning
confidence: 99%
“…Several types of factors, which generally have been investigated separately in the previous literature, have been verified to influence the validity of the EKC hypothesis, and they include: (1) pollutant indicators––such as flow pollutants (e.g., SO 2 and NO x ), which cause immediate damage and elicit constant pressure on the administrative authorities, and stock pollutants (e.g., CO 2 and heavy metal wastes), which harm the environment later and long into the future, and which some myopic governments allow to grow with income [ 18 ]; (2) regional discrepancies––which are especially salient because economic scale and income accumulation remain significantly unbalanced across the eastern, middle, and western regional divisions in China [ 2 , 19 ]; (3) trade openness and technology aggregation––which imply that increasing scale effects arise from production expansion, that composition effects arise due to the shifting of “dirty” industries, and that technique effects occur because of the advancement of technology and distribution [ 1 , 13 , 19 ]; (4) the industrial and energy structure––which, because China’s energy consumption structure remains coal-dominated, its rapid industrialization would stimulate rigid demands for energy and present sustained growth of pollutant emissions [ 3 , 16 ]; (5) governments’ environmental regulation and policy preferences––which, in the face of fundamentally conflicting objectives between economic growth and environmental preservation, can cause local governments to tend to strategically implement top-down environmental regulations, consequently leading to varying income–pollution nexuses in different localities [ 3 , 20 ]; and (6) pollution diffusion––which is salient because geographically adjacent regions share many characteristics in terms of factor endowments, development patterns, and institutional environments that may cause them to present an interactive strategy for emissions reduction, as well as an interrelated income–pollution nexus [ 21 , 22 ] (as shown in Table 1 ).…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%